The Industrial Engineer, His Philosophy and the Scope of His Activities - Delaney, Walter (Relations industrielles / Industrial Relations, 1954)
Summary Opinions concerning the industrial engineer are various. Everyone knows that engineers, chemists, biologists, botanists had their valuable contribution in the evolution of industrialism, but what is the Industrial Engineer's role ? Does he work towards the same end ? What is his philosophy and the scope of his activities ? What methods and techniques does he use in order to bring progress in industry ? There are all interesting questions to which the author gives an answer in this short article.